The effect of bariatric surgery on serum 25‐OH vitamin D levels: a systematic review and meta‐analysis. (27th June 2017) - Kalani, A.; Bami, H.; Tiboni, M.; Jaeschke, R.; Adachi, J. D.; Lau, A. N.
Summary: Background: Concerns have emerged about post‐operative decreases in calcium and vitamin D following bariatric surgery. This review explores changes in metabolic bone health in persons with obesity undergoing gastric bypass surgery compared to non‐surgical controls, providing an updated and comprehensive perspective on the literature. Methods: An electronic search was conducted in MEDLINE, Pubmed, EMBASE and Cochrane databases to 8 November 2016. Eligible trials included randomized controlled trials or controlled observational studies of patients who have undergone laparoscopic gastric bypass surgery. Statistical analysis was carried out using the Cochrane Collaboration Review Manager (RevMan 5.0), and a random effects model was implemented. Outcomes were expressed as weighted mean difference (WMD). The primary outcome examined was change in 25‐OH‐D levels at 12 months post surgery, and secondary outcomes included change in bone mineral density (BMD) measurements at 12 months post surgery at the lumbar spine (LS) and total hip (TH). Results: At 12 months, there was no significant difference in 25‐OH vitamin D in the surgical group compared to controls (WMD = 6.79%; 95% CI: −9.01, 22.59; p = 0.40; I 2 = 68%). There was no statistically significant difference between fracture risk in the surgical population compared to controls (RR = 1.24; 95% CI: 0.99, 1.56; p = 0.06; I 2 = 0%). A significant BMD reduction was however shown at the TH (WMD, −7.33%, 95% CI = −8.70 to −5.97, p < .001, I 2 = 0%), and a trend towards decline was observed at the LS (WMD, −1.73%, 95% CI = −3.56 to 0.11, p = 0.06, I 2 = 0%). Changes at 24 months for applicable outcomes were similar to the results at 12 months. Conclusions: Bariatric surgery may compromise metabolic bone health, but the paucity of high‐quality literature limits conclusions.